Tracking the Photoactivity At The Interface of SiC/Poly 2(2-Thienyl) Furan Thin Solid Film in Polymer Gel Electrolytes - Kasem Kasem; Hisako Masuda; Andrea Mendez Rodriguez (Journal of Electrochemical Science and Engineering, 2024)
Assemblies made by immobilizing nanoparticles SiC into poly 2(2-thienyl) furane (PTF) were subjected to optical and electrochemical investigation. The studies show that SiC, a molecular inorganic compound, and PTF produce reproducible photo responses. Optical studies show that the optical band gap of SiC is around 2.5 eV while PTF's is around 2.2 eV. The band gap values suggest these assemblies absorb the visible solar radiation spectra. Electrochemical studies in gel electrolytes indicate that PTF and PTF/SiC under illumination show p-p behavior, where hole accumulation dominates. SiC thin films lack such character. Electrochemical Impedance Spectroscopy (EIS) studies revealed that the PTF and PTF/SiC possess kinetic and diffusional charge transfer properties. The studied assemblies and the gel electrolyte showed stability and resistance to photodegradation as evidenced by the regeneration of the same photo response after a longer period of experimentation.